Advancing patient evidence in XLH (APEX): rationale and design of a real-world XLH global data unification program - Brandi, Maria Luisa; Carpenter, Thomas O.; Fukumoto, Seiji; Haffner, Dieter; Imel, Erik A.; Kanematsu, Masanori; McCullough, Keith P.; Ozono, Keiichi (Frontiers in Endocrinology, 2025)
X-linked hypophosphatemia (XLH) is a rare, genetic, progressive, lifelong disorder caused by pathogenic variants in the phosphate-regulating endopeptidase homolog, X-linked (PHEX) gene, resulting in excess fibroblast growth factor 23 (FGF23) and consequent renal phosphate wasting. Chronic hypophosphatemia leads to deficits of the musculoskeletal system affecting bone, muscle, joint, and dental health. XLH treatments include oral phosphate and active vitamin D—which are associated with a burdensome dosing regimen, gastrointestinal disturbances, hyperparathyroidism, and nephrocalcinosis—or burosumab, a fully human anti-FGF23 antibody. Randomized clinical trials (RCTs) demonstrated burosumab to be well tolerated and efficacious in improving serum phosphate, rickets, bone turnover, and patient-reported outcomes. However, there are limited data on the natural history of XLH or real-world comparisons of the safety, effectiveness, and long-term outcomes of XLH treatments. Advancing Patient Evidence in XLH (APEX) is a global data unification project aiming to describe the burden and lifelong progression of XLH, collect real-world data on treatment effectiveness and safety, and investigate regional differences in treatment outcomes. Participants from three observational, noninterventional, retrospective and prospective, multicenter, longitudinal (10-year) studies of patients with XLH will be included: XLH Disease Monitoring Program (NCT03651505), International XLH Registry (NCT03193476), and SUNFLOWER (NCT03745521). Data collected in the Americas, Europe, Israel, Japan, and South Korea will be processed to unify identical and similar data elements. Data unification will be an iterative process with a clinical and programming review, ensuring validity and accuracy. In this observational study, unified data involving approximately 2000 pediatric and adult participants with XLH will be analyzed to address research questions in an exploratory manner. Long-term observational studies and patient registries provide opportunities to generate real-world data and address knowledge gaps in rare diseases. APEX aims to improve clinical decision-making and practice by bridging evidence gaps that cannot be addressed by RCTs or regional registries.